An evaluation of polypharmacy medication reviews in GP practices (Fields, 2017)
Polypharmacy, defined as the concurrent use of four or more medications by a single patient, is ever-increasing. It enhances the risk of adverse drug reactions (ADRs) and can represent a huge burden to patients. Medication reviews are the proposed panacea for reducing such problematic polypharmacy. These reviews conducted on patients aged 65 years or over can be aided by activation of the STOPP/START toolkit, an electronic tool that gives alerts, specific to a patient’s current medication regime, to recommend that GPs stop and/or start certain medications. Unique to this toolkit, the alerts are significantly associated with the Royal College of General Practitioners (RCGP) prescribing safety indicators – indicators designed to reduce ADRs – and, thus, the toolkit attempts to enhance patient safety. The aim of this study was to determine whether the STOPP/START toolkit improves medication reviews conducted on elderly polypharmacy patients.